Latinos and American Law: Landmark Supreme Court Cases - Bender, Steven W. (The American journal of legal history, 2006)
In this review, the author advocates for a work which provides much needed attention to Latinos in the context of American Law. Specifically, the review outlines key elements of Soltero’s work, which highlights Latino Supreme Court cases